2021
DOI: 10.1101/2021.08.24.456354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PU.1 and MYC transcriptional network defines synergistic drug responses to KIT and LSD1 inhibition in acute myeloid leukemia

Abstract: Activating mutations in the KIT tyrosine receptor kinase confer an adverse prognosis for patients with acute myeloid leukemia (AML). Successful treatment options are limited, as kinase inhibition monotherapy for AML is often followed by rapid drug resistance. Here we demonstrate that combined KIT and LSD1 inhibition causes increased cytotoxicity and may mitigate the propensity for relapse with kinase inhibition. This combination suppresses MYC at both the transcript and protein level to drive cell cycle exit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…In our model, genes upregulate by the combination of LSD1 and JAK inhibition were enriched for PU.1 and Runx1 motifs ( Figure 7 ). These findings are in line with previous studies of LSD1 inhibition in leukemia showing activation of PU.1 targets in MLL-rearranged AML 19,20 and KIT-mutant AML 21 .…”
Section: Discussionsupporting
confidence: 93%
“…In our model, genes upregulate by the combination of LSD1 and JAK inhibition were enriched for PU.1 and Runx1 motifs ( Figure 7 ). These findings are in line with previous studies of LSD1 inhibition in leukemia showing activation of PU.1 targets in MLL-rearranged AML 19,20 and KIT-mutant AML 21 .…”
Section: Discussionsupporting
confidence: 93%
“…However, the MYC BENC is bound by many other transcription factors, indicating that drug combination efficacy may be dependent on interruption of other MYC BENC-bound factors. Prior studies have shown that LSD1 inhibitor monotherapy decreases MYC expression (20)(21)(22). A critical component of LSD1-inhibitor efficacy is the disruption of LSD1 scaffolding of GFI1 from the CoREST transcription repressor complex (25).…”
Section: Lsd1 Inhibition Represses the Expression Of Myc And Its Targ...mentioning
confidence: 99%
“…Prior work from our lab and others suggest that the combination of kinase and LSD1 inhibition may be an effective therapeutic strategy in AML (20)(21)(22)(23). To establish whether this approach is effective for FLT3-ITD AML, we treated FLT3-ITD-positive (MOLM13 and MV4-11) and FLT3-ITD-negative (K562) cell lines with multiple FLT3/LSD1 inhibitors.…”
Section: Combined Flt3/lsd1 Inhibition Synergistically Represses Myc ...mentioning
confidence: 99%
See 2 more Smart Citations